2012
DOI: 10.1016/j.rppneu.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Infeção por staphylococcus aureus meticilina-resistente da comunidade em Portugal

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has recently emerged as a cause of community-acquired infections among individuals without risk factors. Community-associated MRSA (CA-MRSA) appears to be more virulent, causing superficial mild skin and soft tissue infections to severe necrotizing fasciitis, and in rare cases, pneumonia. Community-associated MRSA was first reported in Australia in the early 80s, after almost two decades in the USA, and then in several countries in Europe, Asia and South Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“… 16 There is evidence that mothers of preterm infants have lower success rates in breastfeeding, and thus the adoption of practices that aim to establish and maintain the supply of breast milk as first choice for feeding preterm infants, considered a vulnerable population, must be continually supported and reviewed. 1 , 5 - 7 , 17 …”
Section: Discussionmentioning
confidence: 99%
“… 16 There is evidence that mothers of preterm infants have lower success rates in breastfeeding, and thus the adoption of practices that aim to establish and maintain the supply of breast milk as first choice for feeding preterm infants, considered a vulnerable population, must be continually supported and reviewed. 1 , 5 - 7 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Studies including isolates from nasal swabs of young healthy individuals, nasopharyngeal swabs of children attending day care centers and isolates from soft tissues infections (SSTI) in children attending a pediatric emergency department, reported a prevalence of MRSA lower than 0.9% [12][14]. Typically CA-MRSA clonal lineages, as the European clone (ST80-IVc) or the USA300 clone (ST8-IVa) producing PVL, were sporadically reported in Portugal only in cases where the existence of hospital risk factors could not be eliminated [12], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…22 Some studies have reported high rates of MRSA in SSSI or similar infections, both CA-MRSA and HA-MRSA, ranging from 22.4% to 74.8%, 1,12 but with important geographic variations. 23 In Portugal CA-MRSA has already been reported, 24 but HA-MRSA clearly predominates.…”
Section: Discussionmentioning
confidence: 99%